Periodontal disease risk factors in elderly and older adults with diabetes mellitus comorbidity using the PRECEDE–PROCEED framework: a cross-sectional study - Sabdho Wening, Gilang Rasuna; Mayasari, Yufitri; Kherul Anuwar, Ainol Haniza; Putra, M. Daffa Refasyah; Putri, Rinta Giska (Padjadjaran Journal of Dentistry, 2026)
Introduction: Diabetes mellitus (DM) increases the risk and severity of periodontal disease, particularly among elderly populations. Behavioral and contextual determinants may further exacerbate periodontal vulnerability in individuals with DM. This study aimed to describe periodontal disease risk factors among elderly and older adults with diabetes mellitus using the PRECEDE framework, focusing on predisposing, reinforcing, and enabling factors. Methods: A descriptive cross-sectional study was conducted among 33 elderly and older adults with confirmed diabetes mellitus at the Dukuh Kupang Primary Health Center, Surabaya, Indonesia. Data were collected using structured questionnaires assessing predisposing (knowledge, dietary adherence, physical activity, medication use), reinforcing (family and healthcare support), and enabling factors (health service utilization), alongside clinical periodontal examination using the Harald Löe Plaque Index. Data were analyzed descriptively and presented as frequencies and percentages. Results:  Periodontal risk was categorized as moderate in 51.5% and high in 48.5% of respondents. Predisposing factors showed that 72.7% did not regulate food portions, 54.5% did not adhere to physician-recommended diets, 42.4% did not exercise regularly, and 21.2% did not consistently take antidiabetic medication. Reinforcing factors indicated that 39.4% reported limited family support for medication adherence and 18.2% reported insufficient health education support. Enabling factors revealed that 15.2% did not undergo regular blood glucose examinations and 18.2% did not routinely record glucose levels. Clinically, 57.6% had plaque index scores above the mean, indicating substantial plaque accumulation. Conclusion: Periodontal vulnerability among elderly individuals with diabetes mellitus is characterized by a convergence of unfavorable predisposing (21.2–72.7%), reinforcing (18.2–39.4%), and enabling (15.2–18.2%) factors. Strengthening behavioral modification strategies, social support systems, and structured diabetes monitoring within primary healthcare settings may be important to reduce the burden of periodontal disease.